2021
DOI: 10.1097/olq.0000000000001404
|View full text |Cite
|
Sign up to set email alerts
|

The Population-Level Effect of Screening for Mycoplasma genitalium on Antimicrobial Resistance: A Quasi-Experimental Study

Abstract: Background: No studies have evaluated the utility and risks of screening for Mycoplasma genitalium in men who have sex with men taking preexposure prophylaxis (PrEP). We made use of a quasi-experimental design to evaluate the effect of screening for M. genitalium in a demonstration PrEP cohort with 3-monthly follow-up. Methods:We compared the proportion of PrEP participants with M. genitalium clearance, the duration of persistence, proportion with incident symptoms, the incidence of fluoroquinolone and macroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In addition, half of the infections cleared by the next visit and almost 75% of these infections cleared without receipt of treatment. This is in line with a PrEP study performed in Belgium among MSM in which almost half of the MG infections that did not receive treatment cleared spontaneously [ 23 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, half of the infections cleared by the next visit and almost 75% of these infections cleared without receipt of treatment. This is in line with a PrEP study performed in Belgium among MSM in which almost half of the MG infections that did not receive treatment cleared spontaneously [ 23 ].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, half of the MG infections with ParC 83/87 alterations cleared the infection by the next visit. Natural clearance of MG infections with fluoroquinolone RAMs was previously described, and the authors suggested that this could be explained by fluoroquinolone RAMs conferring a fitness cost [ 23 ]. As such, clinical fluoroquinolone resistance may be overestimated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The cessation of MG screening led to a 38- and 2-fold decline in fluoroquinolone and macrolide consumption respectively but no appreciable increase in symptomatic or asymptomatic MG infections over the subsequent 12 months. 45 Similarly, reducing NG/CT screening resulted in an additional 6-fold reduction in macrolide exposure without any noticeable effect on numbers of symptomatic infections. 46 …”
Section: N Gonorrhoeae C Trachomatis And...mentioning
confidence: 99%
“…What is less clear is what underpins the global variations in macrolide resistance in Mycoplasma genitalium? Various studies have clearly established that exposure to macrolides is a primary driver of macrolide resistance in a number of bacterial species including the related species, Mycoplasma genitalium [2][3][4][5][6]. This has included ecological type studies that have established that population-level consumption of macrolides is positively associated with the prevalence of macrolide resistance in a number of these species [4,5,7].…”
Section: Introductionmentioning
confidence: 99%